EXPLORING STUDENT-TEACHERS' CHALLENGES IN SELECTING LEARNING MEDIA IN DESIGNING TEACHING INSTRUCTIONS: A STUDY IN ENGLISH EDUCATION STUDY PROGRAM - Riry, Jholie Grace Imanuella; Bynnendyk, Sophia; Loppies, Hellien Jacquelin (Pattimura University, 2023)
The objectives of this research are explore the challenges faced by students-teachers from English Language Education Study Program in selecting learning media in designing teaching instructions and to identify strategies to overcome challenges. The gap between this study and previous study is almost no research has been conducted regarding the challenges faced by student-teachers, especially from English Language Education Study Program. Much of the research focused on investigating the challenges faced by student-teachers in designing lesson plans and teaching practices (Nasution & Nisa, 2018; Alanazi, 2019; and Aldabbus, 2020. The data collected from student-teacher batch 2018 & 2019 at English Education Study Program, Faculty of Teacher Training and Education, Pattimura University. This study used explanatory sequential design as research method, whereas the quantitative data were collected using questionnaire to 34 student-teacher who have finished offering the Reflective Microteaching class. The interview was conducted to support the data from the questionnaire. The researcher collected the qualitative data by using the interview with 4 selected student-teacher with different final score they get in Reflective Microteaching class. Researcher used 1 data techniques in analyzing data, descriptive statistics percentage. The findings showed that student-teachers faced some challenges in selecting learning media in designing teaching instruction, including lack of cost, time, references, and ideas based on the result of the questionnaire analysis. Furthermore, student-teacher also found some strategies to overcome the challenges, including searching on internet and discuss with lecturer.